Digitalisation of Teaching Materials for Toba Batak Ethnic Decorative Variety with Procreate Media Based on p-Books and e-Books - Azis, Adek Cerah Kurnia; Lubis, Siti Khodijah; Kartono, Gamal; Daulay, Muhammad Anggie Januarsyah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to develop teaching materials in the form of digitalisation of Toba Batak Ethnic Decorative Variety with p-book and e-book-based procreate media that are valid, practical, and effective in the Fine Arts Department. This research method uses research and development with the 4-D development model (Four-D Models), namely define, design, develop, and disseminate. This research instrument uses a questionnaire with a Likert scale, while the data analysis technique consists of analysing the validity, practicality and effectiveness of teaching materials. The results of this study indicate that: a) p-book and e-book-based teaching materials with the title of the book/module/teaching material "Gorga Batak Toba", with the acquisition of a category that is quite valid with an average score of 78%, b) teaching materials are quite practical to be used by students in the North Sumatra Ethnic Decorative Variety Course (RHESU) with a score of 77%, and c) teaching materials fall into an effective category where students from four categories such as reading teaching materials, asking questions, answering questions, and completing assignments given by lecturers, can be observed in the learning process and student learning outcomes are 83.26%. So, from the scores and test results of the research results above, it can be said that the teaching materials are quite valid, quite practical, and effective to be applied in learning the North Sumatra Ethnic Decorative Variety Course (RHESU) at the Department of Fine Arts, Faculty of Language and Arts, Universitas Negeri Medan.